Deficiency of ribosomal protein S26, which is mutated in a subset of patients with Diamond Blackfan anemia, impairs erythroid differentiation - Piantanida, Noemy; La Vecchia, Marta; Sculco, Marika; Talmon, Maria; Palattella, Gioele; Kurita, Ryo; Nakamura, Yukio; Ronchi, Antonella Ellena; Dianzani, Irma; Ellis, Steven R.; Fresu, Luigia Grazia; Aspesi, Anna (Frontiers in Genetics, 2022)
Diamond Blackfan anemia (DBA) is a rare congenital disease characterized by defective maturation of the erythroid progenitors in the bone marrow, for which treatment involves steroids, chronic transfusions, or hematopoietic stem cells transplantation. DBA is caused by defective ribosome biogenesis due to heterozygous pathogenic variants in one of 19 ribosomal protein (RP) genes. The decreased number of functional ribosomes leads to the activation of pro-apoptotic pathways and to the reduced translation of key genes for erythropoiesis. Here we characterized the phenotype of RPS26-deficiency in a cell line derived from human umbilical cord blood erythroid progenitors (HUDEP cells). This model recapitulates cellular hallmarks of DBA including: imbalanced production of ribosomal RNAs, upregulation of pro-apoptotic genes and reduced viability, and shows increased levels of intracellular calcium. Evaluation of the expression of erythroid markers revealed the impairment of erythroid differentiation in RPS26-silenced cells compared to control cells. In conclusion, for the first time we assessed the effect of RPS26 deficiency in an erythroid progenitor cell line and demonstrated that these cells can be used as a scalable model system to study aspects of DBA pathophysiology that have been refractory to detailed investigation because of the paucity of specific cell types affected in this disorder.